Gastrointestinal pythiosis with concurrent presumptive gastrointestinal basidiobolomycosis in a Boxer dog. (21st March 2019) - Parambeth, Joseph C.; Lawhon, Sara D.; Mansell, Joanne; Wu, Jing; Clark, Sabrina D.; Sutton, Deanna; Gibas, Connie; Wiederhold, Nathan P.; Myers, Alexandra N.; Johnson, Mark C.; Levine, Gwendolyn J.; Schlemmer, Samantha; et al.
Abstract: A 2‐year‐old female spayed Boxer dog was presented for a 1‐month history of progressive hemorrhagic diarrhea with tenesmus and weight loss despite trial courses of antibiotics and diet change. Abdominal ultrasound revealed severe, focal thickening, and loss of normal architecture of the colonic wall with abdominal lymphadenomegaly. Dry‐mount fecal cytology, performed on several consecutive days, consistently revealed numerous, round, 16‐20 μm structures with basophilic, granular content, and a thin cell wall. Transmission electron microscopy identified these structures as fungi. Culture, polymerase chain reaction (PCR), and sequencing of the internal transcribed spacer, D1/D2 regions, and DNA‐directed RNA polymerase II core subunit (RPB2) confirmed the presence of Basidiobolus microsporus in the feces. Biopsies collected via ileocolonoscopy revealed marked, multifocal, chronic, neutrophilic, and eosinophilic ileitis and colitis with ulceration, granulation tissue, and intralesional hyphae (identified with Gomori methenamine silver stain). A Pythium enzyme‐linked immunosorbent assay and Pythium ‐specific PCR performed on the formalin‐fixed paraffin‐embedded biopsy specimens were positive while Basidiobolus ‐specific PCR was negative, thus confirming a diagnosis of pythiosis. This report describes a fatal case of colonic and intestinal pythiosis with the presence of fecal Basidiobolus sp. spores, suggestive of concurrent gastrointestinal basidiobolomycosis.